Pyramid pooling enhanced ResUNet for accurate 3D brain image segmentation - Mollah, Md. Shawon; Ahmed, Farhan Tanvir; Chowdhury, Mahjabin; Ahmed, Iftekhar; Hasan, S. M. Rakib (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.